Alcohol affordability: implications for alcohol price policies. A cross-sectional analysis in middle and older adults from UK Biobank. (9th April 2021) - Moore, Simon C; Orpen, Bella; Smith, Jesse; Sarkar, Chinmoy; Li, Chenlu; Shepherd, Jonathan; Bauermeister, Sarah
Abstract: Background: Increasing the price of alcohol reduces alcohol consumption and harm. The role of food complementarity, transaction costs and inflation on alcohol demand are determined and discussed in relation to alcohol price policies. Methods: UK Biobank ( N = 502, 628) was linked by region to retail price quotes for the years 2007 to 2010. The log residual food and alcohol prices, and alcohol availability were regressed onto log daily alcohol consumption. Model standard errors were adjusted for clustering by region. Results: Associations with alcohol consumption were found for alcohol price ( β = −0.56, 95% CI, −0.92 to −0.20) and availability ( β = 0.06, 95% CI, 0.04 to 0.07). Introducing, food price reduced the alcohol price consumption association ( β = −0.26, 95% CI, −0.50 to −0.03). Alcohol ( B = 0.001, 95% CI, 0.0004 to 0.001) and food ( B = 0.001, 95% CI, 0.0005 to 0.0006) price increased with time and were associated ( ρ = 0.57, P < 0.001). Conclusion: Alcohol and food are complements, and the price elasticity of alcohol reduces when the effect of food price is accounted for. Transaction costs did not affect the alcohol price consumption relationship. Fixed alcohol price policies are susceptible to inflation.